The sequestrate genus Rhodactina (Basidiomycota, Boletales) in northern Thailand - Zhu L. Yang (2018)
The sequestrate Rhodactina was originally proposed as a monotypic genus to accommodate R. himalayensis and was suggested be a member of the Gautieriaceae because of similarities in spore ornamentation. Our results, based on atp6 sequences, however, place Rhodactina in the Boletaceae. In addition to the type species, a new species, R. incarnata, from northern Thailand is described and illustrated.